Screening for a practical method to monitor the status of patients with metastatic bladder cancer at the circulating cell-gene level - Ryota Ogura; Saya Ito; Takashi Ueda; Yusuke Gabata; Satoshi Sako; Yuta Inoue; Takeshi Yamada; Hirotaka Konishi; Atsuko Fujihara; Osamu Ukimura (Scientific Reports, 2023)
Abstract Identifying a novel method to monitor metastatic bladder cancer status at the cell-gene level could lead to earlier appropriate therapeutic intervention and better outcomes. In this study, we evaluated a practical method to monitor the cancer status at the circulating cell-gene level before and after treatment in fourteen patients with metastatic bladder cancer who were indicated for systemic drug therapy. Patients were assessed via imaging before and after drug treatment, and cell-free DNA (cfDNA) analysis was performed to detect three parameters: cfDNA level, ERRB2 gene copy numbers, and telomerase reverse transcriptase (TERT) gene mutations. We hypothesized that decreased cfDNA levels, a normal copy number of ERB-B2 receptor tyrosine kinase 2 (ERBB2), and the absence of the TERT C228T mutation indicate cancer suppression. We found that a > 1.8-fold increase in cfDNA levels, increased copy number of ERBB2, or the existence of the TERT C228T mutation indicated disease progression. Stable cfDNA levels, normal ERBB2 copy number, and the absence of TERT C228T mutations indicate a stable cancer status. Collectively, our results show that the combination of cfDNA concentration, TERT mutation, and ERBB2 copy number may be useful for determining the efficacy of drug therapy in patients with metastatic bladder cancer.